Pemberian Terapi Murotal Al Qur’an pada Peserta Didik SLBN 2 Palangka Raya untuk Meningkatkan Kecakapan Hidup - Dwi Sari Usop; Misyanto Misyanto (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
The provision of Murotal Al Qur'an therapy aims to improve the life skills of students at SLBN 2 Palangka Raya as it is known that the Al Qur'an is a guide for the life of Muslims. The results of the research show that listening to the Murotal Al Qur'an can have a calming effect on the listener so that it can improve the quality of sleep for children with mental disabilities who have difficulty sleeping. Apart from psychological effects, physiological effects are also felt by using Murotal Al Qur'an therapy. In general, giving Murotal Al Qur'an Surat Ar Rahman therapy to students at SLBN 2 Palangka Raya has a calming effect. Some students tend to be active, like walking around in the room. Some may be asked to sit and listen to the chanting of the verses of QS Ar Rahman. Some of them prefer to be active, touch or hold objects in the school prayer room that attracts their attention. Some take the prayer mat and perform the prayer movements.